The impact of emotional distress on suicidal ideation in head and neck cancer patients: A review - Priya Baluni; Ravindra Singh; Rishima Bhutani; Anushka Mishra (Oral Oncology Reports)
Suicide is a notable cause of mortality worldwide, with cancer patients having almost double the rate of suicide deaths compared to the general US population. Living with head and neck cancer is psychologically and emotionally distressing for the patient. Effects of treatment such as ingestion impairment, communication impediment, aesthetic compromise, and hindrance to breathing all contribute to their emotional distress. This review aims to investigate the impact of emotional distress and suicidal ideation in Head and Neck Cancer patients. Empirical studies as well as review papers were utilized to gather relevant information from databases such as Google Search, Google Scholar, PubMed, ScienceDirect. The following search terms were used; ‘Emotional Distress’, ‘Psychological Response’, ‘Emotional Response’, ‘Suicide’, ‘Suicide in Cancer’, and ‘Suicidal thoughts in Head and Neck Cancer'. 30 articles matching the theme of our review were considered for data synthesis. The findings of the previous studies reveal a strong positive correlation between emotional distress and suicidal ideation in Head and Neck cancer. In addition to the existing findings, emotional distress was also correlated with poor quality of life and physical symptoms. In conclusion, the treatment of cancer-associated distress is equally crucial as the treatment of the physical illness. Moreover, emotional support can significantly reduce the level of emotional distress and suicidal ideation and elevate the chances of speedy recovery in those patients. Future research must address the psychological demands of Head and Neck cancer patients and offer an effective therapeutic intervention.